The capacity of patients to make decisions in health: attitude and Meaning for physicians and lawyers - Bórquez Estefo, Gladys; Horwitz Campos, Nina; López Bravo, Ilse; Raineri Bernain, Gina (Acta Bioethica, 2008)
The objective of this article is to examine the attitudes of a group of physicians and lawyers that practice in Santiago, Chile toward the application of a protocol which evaluates the capacity of patients to make autonomous health decisions. The responses were grouped in four dimensions: assessment, feasibility, acceptance and usefulness. The Wilocoxon rank-sum test was applied to evaluate the distribution significance of value differences. The results revealed a globally positive assessment of lawyers and physicians to the pertinence and usefulness of standardization of procedures. The physicians emphasized the practical aspects and the lawyers, protection of patient autonomy and human rights. Consideration of the opinions of medical and legal actors is indispensable when a civic bioethics is founded in ethical dialogue.